THE INFLUENCE OF INVESTMENT DECISIONS, DEBT POLICY, ACCOUNTING CONSERVATISM, INTELLECTUAL CAPITAL AND GOOD CORPORATE GOVERNANCE ON COMPANY VALUE - Suci Lestari; Nafi' Inayati Zahro; Diah Ayu Susanti (Kajian Akuntansi, 2023)
This study aims to empirically examine the influence of investment decisions, debt policies, accounting conservatism, intellectual capital and good corporate governance on company value in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. Determination of samples using purposive sampling method with a total sample of 94 companies studied. This study used multiple linear regression analysis techniques using SPSS version 25. The results in this study show that investment decisions, debt policy, accounting conservatism, managerial ownership and institutional ownership have no effect on company value, while intellectual capital has a positive effect on company value. Keywords: Investment Decision, Debt Policy, Accounting Conservatism, Intellectual Capital, Good Corporate Governance, Firm Value.